Chinese Water Systems Volume 4: Applied Water Management in China - Dohmann, Max.; Grambow, Martin; Song, Yonghui; Wermter, Paul.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open-access book addresses latest Sino-German results of the joint research efforts within Major Water Program of the Chinese Government supported by German research funding. The Major Water Program aims at the restoration of polluted water environments and sustainable management of water resources in China. The joint BMBF-CLIENT project SINOWATER deals with three most significant and strongest polluted Chinese waters, the river Liao and the Dian-lake as well as Tai-lake in the area of the metropolises Shenyang, Kunming and Suzhou, respectively. The project was conducted by the Research Institute for Water and Waste Management at RWTH Aachen (FiW) e.V., Bavarian State Ministry of the Environment and Consumer Protection, Technical University of Munich, RWTH Aachen University, German and Chinese companies (Martin Membrane Systems AG, Steinhardt GmbH Wassertechnik, GuHong, JT-elektronik, bluemetric, Huawang Water, EVU Group, Atemis GmbH, i+f process GmbH) in close cooperation withChinese Academy of Environmental Sciences, Tongji University, and the Dianchi Lake Management Authorities. Overall, the joint Sino-German research project SINOWATER provided solutions for the improvement of the water quality in the mentioned water bodies as well as development and optimization of Good Water Governance. These objectives could be achieved through the implementation of innovative German water technologies and the optimization of water management elements in the fields of industrial and municipal wastewater treatment as well as river and shallow lake management.
1. Improving water management and the water management system in the Liao river basin and Lake Dian -- 2. Ecological indicators for surface water quality-methodological approaches to fish community assessments in China and Germany -- 3. Dianchi Shallow Lake Management -- 4. New technical approaches for the co-processing of pharmaceutical wastewater in municipal wastewater treatment plants in the Shenyang region -- 5. The planning, management and decision support systems of Kunming$1 (Bs urban drainage system -- 6. Treatment of wastewater with high proportion of industrial wastewater with extreme requirements on the elimination of nutrients -- 7. Adaption and introduction of German sewer inspection technology in China.s
Keywords: Refuse and refuse disposal; Water; Hydrology; Computer science; Geotechnical engineering; Engineering geology; Waste Management/Waste Technology; Water; Computer Science; Geotechnical Engineering and Applied Earth Sciences; Geoengineering